1999
DOI: 10.1046/j.1439-0264.1999.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Ultrastructural Study of Carpal Organ in Adult Female Wild Swine

Abstract: The carpal organ of adult female wild swine is a sweat-type gland which secretes an odorous substance. The gland consists of 5-7 lobes, each made up of lobules with convoluted glandular tubules. The gland secretion is transported in large excretory canals which empty from 5 to 7 clearly visible pores. An ultrastructural examination showed that the glandular tubules are made up of single-layered epithelium with different types of cells. One type, with rather electron-dense cytoplasm, is secretory cells full of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 0 publications
6
12
0
Order By: Relevance
“…Results from our histological analysis agree with previous studies made on the histology, histochemistry and ultrastructure of this gland in domestic pigs (Filotto 1950, Gargiulo et al 1989) and wild boars (Hraste & Stojković 1995, Farnesi et al 1999). The method of secretion is merocrine for some authors, but apocrine for others.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Results from our histological analysis agree with previous studies made on the histology, histochemistry and ultrastructure of this gland in domestic pigs (Filotto 1950, Gargiulo et al 1989) and wild boars (Hraste & Stojković 1995, Farnesi et al 1999). The method of secretion is merocrine for some authors, but apocrine for others.…”
Section: Discussionsupporting
confidence: 91%
“…The method of secretion is merocrine for some authors, but apocrine for others. In support of the first hypothesis, light and dark cells typical of the merocrine sweat glands have been observed (Farnesi et al 1999; Figure 3D), even if different thicknesses in the secretory epithelium in adjacent secretory units ( Figure 3B), as well as the apical cell protrusions in the lumen ( Figure 3C) indicate that apocrine secretion is predominant. A particular apocrine secretion was previously described in an ultrastructural study of the pig carpal gland, in which the granules released were enclosed within their membrane (Gargiulo et al 1989).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In addition, the glands were larger in sexually mature/ reproductively-active females. No seasonal variation is size is observed in the males as reported by Farnesi et al [72], Heise-Pavlov et al [73]. Bacchetta et al [74] reported that males had more developed and functional glands than females, with the oldest males having the highest values of gland surface, gland thickness and tubule diameter.…”
Section: Each Of the Aspects Of Wild Pig Behavior Is Discussed Separamentioning
confidence: 71%